Prospects of the Intelligent Driving Technology for Autonomous-rail Rapid Tram - FENG Jianghua; HU Yunqing; XIAO Lei; YUAN Xiwen; PAN Wenbo; LIN Jun; LIU Yue (Kongzhi Yu Xinxi Jishu)
In face of the rapid emergence of new technologies and the increasing customers’ demands, autonomous-rail rapid tram will be taken as a platform for new intelligent technologies application, so as to improve its intelligent level continually. In the future, the application coverage will be extended from vehicle to ground equipment and infrastructure. This article looks forward to the technical framework and development of intelligent driving technology for autonomous-rail rapid tram.